2012
DOI: 10.1124/mol.111.076976
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase Mitogen-Activated Protein Kinase-Dependent SOCS-3 Gene Induction Requires c-Jun, Signal Transducer and Activator of Transcription 3, and Specificity Protein 3 Transcription Factors

Abstract: SOCS-3 gene induction by cAMP-elevating agents or the protein kinase C (PKC) activator, phorbol 12-myristate 13-acetate (PMA), in primary HUVECs was found to require PKC-and PKC-dependent extracellular signal-regulated kinase (ERK) activation. The minimal, ERK-responsive element of the SOCS-3 promoter was localized to a region spanning nucleotides Ϫ107 to the transcription start site and contains conserved binding sites for AP-1 and SP1/SP3 transcription factors, as well as proximal and distal signal transduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 49 publications
(84 reference statements)
2
31
0
Order By: Relevance
“…We first examined the effects of naringenin on IL-6-regulated STAT3 activation, since STAT3 is a principle regulator of SOCS3 expression in HUVECs [24]. We found that a 5 h treatment with 100 μM naringenin was able to significantly suppress the ability of IL-6 (5 ng/ml) to promote the activation-dependent Tyr 705 phosphorylation of STAT3 in HUVECs [28.6±3.1% reduction ( n =3, P <0.001); Figure 2a].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined the effects of naringenin on IL-6-regulated STAT3 activation, since STAT3 is a principle regulator of SOCS3 expression in HUVECs [24]. We found that a 5 h treatment with 100 μM naringenin was able to significantly suppress the ability of IL-6 (5 ng/ml) to promote the activation-dependent Tyr 705 phosphorylation of STAT3 in HUVECs [28.6±3.1% reduction ( n =3, P <0.001); Figure 2a].…”
Section: Resultsmentioning
confidence: 99%
“…To this end we tested the ability of compound C to inhibit SOCS3 induction promoted by activation of the PKC (protein kinase C) pathway, the JAK/STAT3 signalling pathway and the cAMP cascade, since all of these pathways have previously been implicated in controlling SOCS3 gene induction in HUVECs [10,21,24,29]. We first activated PKC signalling in HUVECs by stimulating cells with the phorbol ester PMA (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…It is increasingly clear that additional mechanisms also contribute to the regulation of SOCS genes expression, some of which are known to be directly or indirectly influenced by RTK activation. For example, it was recently demonstrated that SOCS3 gene promoter contains AP-1 and SP1/SP3 transcription factors binding sites that mediate ERK-dependent activation of SOCS3 [21]. Given the ability of SOCS proteins to modulate RTK signaling, transcriptional regulation of SOCS genes can provide a means of cross-talk between RTKs and other signaling pathways.…”
Section: Socs Proteins In Rtk Regulationmentioning
confidence: 99%
“…In vascular endothelial cells, Epac1 induces the transcriptional activity of CCAAT/enhancer-binding protein through protein kinase Ca and ERK1/2 (Yarwood et al, 2008;Borland et al, 2009;Woolson et al, 2009) and thereby promotes the expression of SOCS-3. Epac1-dependent induction of SOCS-3 inhibits the IL-6 receptor trans-signaling complex and subsequently limits proinflammatory actions of IL-6 in vascular endothelial cells (Parnell et al, 2012;Wiejak et al, 2012;Fig. 7).…”
Section: Epac and The Vasculature 1 Epac And The Endothelial Barrmentioning
confidence: 99%